Cardiac magnetic resonance evaluation of takotsubo cardiomyopathy. (13th July 2021) - Caldeira Da Rocha, R; Picarra, B; Santos, AR; Carias, M; Claudio, F; Pais, J; Carrington, M; Fernandes, R; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Takotsubo Cardiomyopathy(TCM)is a reversible pathology with clinical features practically indistinguishable from AMI.Cardiac magnetic resonance(CMR)is uniquely suited in differentiating TCM from other forms of acute ventricular dysfunction.CMR can also identify potential complications. Purpose: The aim of this study was to characterize TCM features, as well as to evaluate diagnostic and prognostic impact of CMR in these patients. Methods: A 7-years prospective study, which included patients of our center proposed to CMR with presumptive diagnosis of MINOCA based on acute chest pain, troponin raise and absence of angiographically significant coronary disease (luminal stenosis <50%).We analysed clinical characteristics, electrocardiograms, echo and coronariography.A presumptive diagnosis was elaborated and comparison was made with the TCM definitive one after CMR.We applied a protocol to evaluate TCM patients' left and right ventricles(LV;RV)both anatomically and functionally, and search for late gadolinium enhancement(LGE). Results: A total of 93 patients were evaluated, of which 16 had the final diagnosis of TCM.Takotsubo-cardiomyopathy patients were all female, with a mean age of 69 ± 14years old.At admission, 75% had ST segment elevation, so emergent coronariography was performed. The median highest troponin I was 2, 235[1, 30-4, 27]ng/mL.CMR confirmed 25%(n = 4) of presumptive diagnosis of TCM. On the other 75%initial diagnosis was changed to TCM after CMR:50%(n = 6) and 17%(n = 2)of patients had an initial presumptive diagnoses of reperfunded STEMI and NSTEMI, respectively. In 33% the initial diagnosis was myocarditis.From CMR evaluation of TCM patients, left atrial dilation was found in 31%(mean indexed area 18 ± 1, 5cm2/m2).A majority (81%) presented with preserved ejection fraction(EF)(mean LV EF 59 ± 10%).Regional contractility abnormalities were described in 19%, being hypokinesia in all mid and apical segments in 2 cases, and diffuse in one.LV dysfunction was present in 13%(mean LV EF 32 ± 2%) and RV"s in 2cases (mean RV EF 42%), with only one with biventricular EF depression.Mean LV end diastolic indexed volume(EDIV)was 72 ± 23mL/m2, with only 2 with LV dilation(LV EDIV 120 ± 7mL/m2), non had dilated RV.Mild pericardial effusion was found in 38%, mild mitral regurgitation in 8patients and moderate in 1.A complication was registered:LV outflow tract protomesossystolic acceleration with mild anterior leaflet prolapse, without SAM.No LV thrombus was identified.LGE was observed in 2(13%)of patients:in one it was found on the apex, on the other one the pattern was linear intramyocardial on mid segment of inferior septum. Conclusion: CMR provides a noninvasive and multidimensional assessment for evaluation of Takotsubo cardiomyopathy.In our population, performing CMR allowed an initial diagnosis modification in 3/4 of the cases and identification of one complication, both with therapeutic and prognostic implications.